2008
DOI: 10.1177/0363546508325666
|View full text |Cite
|
Sign up to set email alerts
|

Sporting Activity after High Tibial Osteotomy for the Treatment of Medial Compartment Knee Osteoarthritis

Abstract: High tibial osteotomy for the treatment of medial compartment knee osteoarthritis in the active patient demonstrated favorable clinical results and allowed patients to return to sports and recreational activities similar to the preoperative level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
121
2
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(134 citation statements)
references
References 39 publications
4
121
2
7
Order By: Relevance
“…Many researchers have investigated the return to sports and the level of sports activity after total joint replacement and joint preserving surgery for the treatment of osteoarthritis [16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have investigated the return to sports and the level of sports activity after total joint replacement and joint preserving surgery for the treatment of osteoarthritis [16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…While these gait speeds appear to be quite slow, they are typical for this patient population when examined using similar methods to those of the present study. 8,28,34,43 Of note, Salzmann et al 42 have reported that patients scheduled for HTO often maintain an active lifestyle prior to surgery and are able to return to their previous activity levels following surgery. We must also acknowledge that examining changes in muscular function and knee joint loading during more physically demanding activities than gait might have elicited differences between groups.…”
Section: Discussionmentioning
confidence: 99%
“…The sports and physical activities (SPA) performed by patients with knee OA before and after valgus knee osteotomy have been investigated and several reports have been published. [6][7][8] These studies involved patients with a wide range of ages and included younger patients who resumed high-impact sports such as tennis and rugby postoperatively.…”
Section: Introductionmentioning
confidence: 99%